Strategi Penguatan Model Pembelajaran Humanistik dalam Membentuk Karakter Siswa - Nazil Raihanah; Nur Diana Supriyandini; Ansori Ansori (Lembaga Pengembangan Kinerja Dosen, 2026)
The purpose of this study is to highlight various methods that can be used to improve the humanistic learning model in shaping student character at Al Fatah Islamic High School in Jambesari, Bondowoso. This study used a qualitative method that collected data through interviews and observations of students, teachers, and the principal. The results showed that humanistic learning can be implemented through a student-centered learning approach. Strategies such as discussion, self-reflection, giving students freedom of speech, and creating a comfortable and empathetic learning environment can be used. In addition, teachers instill character values ​​through role models, responsibility, and collaboration, and adjust learning based on student characteristics. From the students' perspective, humanistic learning improves their social skills, active involvement, and self-confidence. Meanwhile, through evaluation of attitude-based programs, mentoring, and character building, school policies help achieve this. Obstacles faced include limited time, the number of students, and differences in student backgrounds. Overall, it has been proven that the implementation of the humanistic learning model produces students who are more disciplined, responsible, empathetic, and confident.